A Model for Counselling Cancer Patients - Jevne, Ronna F.; Nekolaichuk, Cheryl L.; Williamson, F. Helen A. (Canadian Journal of Counselling and Psychotherapy, 2007)
Cancer invades the lives of people from all walks of life. Every counsellor can expect to deal with people who face the challenges of this devastating, life- threatening illness. This paper describes a model for counselling cancer patients that integrates the unique features of the cancer experience within a basic counselling framework. This model combines a nine step, problem-solving approach with a biopsychosocial perspective, placing greater emphasis on the person than the problem. Innovative questioning techniques and strategies, embedded within this framework, harness the illness experience as a creative force, carving a pathway to patient empowerment and wellness.